Comparing Student Problem-Solving in Math: Double-Loop vs. Multi-Representational Discourse Models - Dewi Anjani; Nurma Izzati (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
This research was conducted at SMP Negeri 7 Cirebon with quantitative methods. Quasi-Experimental research design in the form of posttest-only control group design. This research uses a purposive sampling technique to determine the research sample. The population in this study were all class VIII SMP Negeri 7 Cirebon. The samples used were class VIII B consisting of 36 students and class VIII D consists of 36 students. Data collection technique uses a test instrument in the form of a posttest in the form of a description. The results showed that there was a significant difference between the application of the double loop problem-solving learning model and the multi representation discourse learning model on students' mathematical problem solving abilities with a significance value of 0,001 less than 0,05 (< 0,05). This difference can also be seen from the results of calculating the average mathematical problem solving ability in the experimental class 1 which applies the double loop problem solving learning model of 75,89 while in experimental class 2 which applies the multi representation discourse learning model of 64,34. So, it can be concluded that the mathematical problem solving abilities of students who apply the double loop problem solving learning model are better than the mathematical problem solving abilities of students who apply the multi-representation discourse learning model to the Pythagorean theorem material